KONSEP NAZHAR DALAM PERNIKAHAN MUBARAKAH DIPONDOK PESANTREN HIDAYATULLAH BALIKPAPAN DALAM PERSPEKTIF HUKUM ISLAM - Zaim Azhar, Muh; Fuad Rifqie Alisyah, Muh (Asosiasi Dosen PTKIS Indonesia, 2023)
This research is motivated by the difference between the theory of the concept of nazhar in Islamand the concept of nazhar in mubarakah marriages at the Hidayatullah Islamic Boarding School,balikpapan, where the concept of nazhar in mubarakah marriage does not only look at the woman who willbe proposed to directly, but there are criteria that are seen in terms of non-physical so that this is what isconsidered in the matchmaking process. Therefore, researchers are interested in digging up information andknowing more deeply about the concept of nazhar in Islam and the wisdom in its law, with the concept ofnazhar in mubarakah marriages, so that the similarities and differences can be examined and later theconcept of nazhar in mubarakah marriages will be reviewed for conformity with Islamic law. This research isdescriptive-analytical in nature which describes the concept of nazhar in mubarakah marriages, thenanalyzes its suitability with Islamic law based on the formulation of the problem and research objectives. Thelocus of this research is the Hidayatullah Islamic Boarding School, Balikpapan. The data collectiontechnique in this study was by direct interviews with respondents, as well as studying documents about themubarakah marriage process. Respondents in this study were members of the steering committee (steeringcommittee), organizing committee (organizing committee) and mubarakah wedding participants, as well asthe people involved in the event. From the results of this study, several aspects were found for thematchmaking process, namely; Religion and institutional idealism, educational background, ethnicity,appearance or physique and wealth. Therefore, researchers did not find a significant difference between thetheory of the concept of nazhar in Islam and the concept of nazhar in Mubarakah marriages, because theconcept is still based on sharia principles even in accordance with the purpose of the sharia being carried out(maqasidus sharia), and the existence of this nazhar concept in marriage mubarakah is intended to avoidpost-marriage conflict, so that the integrity of the household is deemed necessary as the actualization ofpositive values and in accordance with the goals of marriage